An Interval-Valued Fuzzy Soft Set Based Decision Making Approach Considering Weight - Hongwu, Qin; Ma, Xiuqin (2014)
The algorithm to solve fuzzy decision making problems based on interval-valued fuzzy soft sets has been proposed. However, this algorithm can not consider the weight of parameter which is very important for decision maker. In this paper, we propose an interval-valued fuzzy soft set based decision making algorithm considering weight. Finally, an illustrative example is employed to show our contribution.